The Role of Emotional Intelligence as a Moderator of the Influence of Peer Conformity on Juvenile Delinquency - Dewi. Z, Indah Sari (Psikoislamika: Jurnal Psikologi Islam, 2025)
: Juvenile delinquency is behavior carried out by young children due to social neglect so that deviant behavior is formed. Delinquency does not appear without factors influencing it, one of which is when adolescents conform to their peers. The influence of peer conformity on juvenile delinquency is weakened when adolescents have emotional intelligence. By having emotional intelligence, adolescents can express their emotions appropriately and have adaptive emotional regulation. The purpose of this study was to find out whether emotional intelligence can moderate the influence of peer conformity on juvenile delinquency. This study is quantitative with research subjects of as many as 350 adolescents. Measurement using Self Report Delinquency (SRD), Peer Conformity Disposition Scale (PCSD), and Wong and Law Emotional Intelligence Scale (WLEIS) instruments. Data analysis using Moderated Regression Analysis (MRA). The results showed that emotional intelligence did not act as a moderator on the influence of peer conformity on juvenile delinquency (β=0.558; p=0.081).